KAJIAN PUSTAKA POTENSI PEMANFAATAN GREYWATERSEBAGAI AIR SIRAM WC DAN AIR SIRAM TANAMAN DI RUMAH TANGGA - Handayani, Dwi Siwi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2013)
ABSTRACT The  level  of  water  service  coverage  in  Indonesia  is less  than  60  %  at  2011.  The  one  reason  is because  of  the  scarcity  of  raw  water  both  in  quantity  and  quality.  Besides  the  level  of  service coverage,  Indonesia  face  to  the  environmental  degradation  specially  Pantura  area  with landsubsidence  and  abrassion  by  the  sea  water.  It  is  because  of  over  extraction  of  groundwater  to fulfill  water  demand  people  who  did  not  served  by  PDAM.  Indonesia  also  not  yet  give  attention  on wastewater services. Mostly of greywater goes enterto waterbody directly without treatment through drainage system. So, to economize on using clean water and to crack the greywater goes enter to drainage system is very important to do immediately by using greywater as substitute of water toilet flushing and gardening irrigation. Greywater is domestic waste water excluded feces and urine. Many country have already been using greywater for toilets flushing and gardening irrigation. The aim of this studi is to know potentially of greywater as toilets flushing and gardening irrigation. The method for data collecting is documentation method with descriptif analysis data method. The results is thatthe  quantity  greywater  generated  from  bathing  each  person  per  day  can  fulfill  demand  of  toilets flushing  each  person  per  day.  The  greywater  generated  from  home  laundry  can  fulfill  demand  of gardening irrigation. But there are some challangespotentially to conduct reusing greywater as toilets flushing and gardening irrigation, such as negativeperception on using it, difficulties on storage it, etc. So, many research topics to cope these challanges have been identified in this study..Keywords: greywater, toilets flushing, gardening irrigation